TAXONOMIC NOTES ON HYPSELOBARBUS SP. DISTRIBUTED ALONG THE SOUTHERN WESTERN GHATS - E, SHERLY WILLIAMS. (Journal of the Inland Fisheries Society of India, 2021)
Morphological characteristics of Hypselobarbus kurali, H. thomassi and H. curmuca were analysed on specimens collected from Southern Western Ghats along Kulathupuzha, Kerala. All the three species were the commonrepresentatives in the fish catch composition of Kulathupuzha during January to December 2011. The study based on the morphological expressions, were useful in sorting these fishes from the fielditself. Morphological characters used were shape of snout, predorsal shape, appearance of auxiliary fin, shape differences in anal fin and colourpattern differences on caudal fin. Freshwater streams in Southeast Asia host a wide variety of fish species (Smith, 1945). According to Sreekantha et al. (2008), fishes inhabiting in running waters have three modes of adaptations (life history, behavioral and morphological) for surviving floods and droughts. The study also emphasied that, fish assemblages in tropical rivers are characterized by high taxonomic diversity